GSTA1 gene variation associated with gestational hypertension and its involvement in pregnancy-related pathogenic conditions. (November 2015) - Iorio, Andrea; Spinelli, Marina; Polimanti, Renato; Lorenzi, Federica; Valensise, Herbert; Manfellotto, Dario; Fuciarelli, Maria
Abstract: Objective(s): Glutathione S-transferases (GSTs) are the main phase II enzymes involved in the cellular detoxification. Through phase I and phase II detoxification reactions, the cell is able to detoxify endogenous and exogenous toxic compounds. In this study, we focused our attention on the GSTA1*-69C/T gene polymorphism (rs3957357) in order to explore its involvement in the genetic predisposition to gestational hypertension (GH). Study design: The case–control population consists of 195 subjects. The genotyping of the GSTA1*-69C/T was performed by using an RFLP-PCR technique. We calculated odds ratios (ORs), adjusted for the confounding variables, to estimate the association between GSTA1 and GH. Results: Significant allelic differences in GSTA1*-69C/T are present between GH women and pregnant women without cardiovascular complications ( p < 0.05). Specifically, we observed that the dominant genetic model best explains the observed genetic association, according to the Akaike information criterion and the Bayesian information criterion. Conclusion(s): Our study highlighted a significant association between the GSTA1 gene and the risk of GH in Italian patients. In particular, the -69C/T variant was significantly associated with disease risk. Since previous studies indicated that this GSTA1 polymorphism is associated with different pregnancy-related conditions, our finding supports the notion that GSTA1 may play a key role during pregnancy.